Guide to the Preparation of Papers for Publication in the Journal of the South African Institute of Mining and Metallurgy (The Southern African Institute of Mining and Metallurgy)
The following notes have been compiled to assist authors in the preparation of papers for presentation to the Institute and for publication in the Journal. All papers must meet the standards set by the Council of the Institute, and for this purpose all papers are referred to at least two referees appointed by Council. STANDARDS FOR ACCEPTANCE To merit consideration papers should conform to the high standards which have been established for publication over many years. Papers on research should contain matter that is new, interpretations that are novel or of new significance and conclusions that cast a fresh light on old ideas. Descriptive papers should not be a repetition of well-known practices or ideas but should incorporate developments which would be of real interest to technical men and of benefit to the mining and metallurgical Industry. In some cases a well prepared review paper can be of value, and will be considered for publication. All papers and particularly research papers, no matter how technical the subject, should be written with the average reader of the Journal in mind, to ensure wide interest. The amount of textbook material included in a contribution should be the minimum essential to the argument. The length of a paper is not the criterion of its worth and it should be as brief and concise as possible, consistent with the lucid presentation of the subject. Only in very exceptional circumstances should a paper exceed 15 pages of the Journal (15 000 words, if there are no tables or diagrams). Six to ten pages is more normal. NOTE: Papers in the Journal are printed in 10 point type, which is larger than the 8 point type used on this page. For special publication Council may decide on page sizes smaller than A4 used for this Journal. The text should be typewritten, double-spaced, on one side only on A4 size paper, leaving a left-hand margin of 4 cm, and should be submitted in duplicate to facilitate the work of the referees and editors. Orthodox sequence Title and author's name, with author's degrees, titles, position. Synopsis. Index, only if paper is long and involved. Introduction, including a brief statement of conclusion. Development of the main substance. Conclusions, in more detail. Acknowledgements. References. Title: This should be as brief as possible, yet give a good idea of the subject and character of the paper. Style: Writing should conform to certain prescribed standards. The Institute is guided in its requirements by: Collins, F. H., Authors & Printers' Dictionary-Oxford University Press. Hart, H. Rules for Compositors and Readers. Humphrey Milford (familiarly known as the Oxford Rules). Fowler, H. W. & F. G. The King's English-Oxford University Press. General: A few well selected diagrams and illustrations are often more pertinent that an amorphous mass of text. Over-statement and dogmatism are jarring and have no place in technical writing. Avoid the use of the first person, be objective and do not include irrelevant or extraneous matter. Avoid unnecessary use of capitals and hyphens, while punctuation should be used sparingly and be governed by the needs of sense and diction. Sentences should be short, uninvolved and unambiguous. Paragraphs should also be short and serve to separate basic ideas into compact groups. Quotation marks should be of the 'single' type for quotations and "double" for quoted matter within quotations. Interpretations in the text should be marked off by parentheses ( ), whereas brackets [ ] are employed to enclose explanatory matter in the text. Words to be printed in italics should be underlined singly. For small capitals they are to be underlined DOUBLY and for large capitals TREBLY. Abbreviations and symbols are laid down in British Standard 1991. Abbreviations are the same for the singular and plural, e.g. cm for centimetre and centimetres, kg for kilogram and kilograms. Percentages are written in the text as per cent; the symbol % is restricted to tables. A full stop after an abbreviation is only used if there is likely to be confusion of meaning. Metric System: The Systemé International d'Unites (S.I.) is to be used for expressing quantities. This is a coherent system of metric units derived from six basic units (metre, kilogramme, second, ampere, kelvin, and candela), from which are derived all other units, e.g. the unit of force is the newton (N) for kilogramme metre per second per second (kg m/s2). Always use the standard metric abbreviations. Commas must not be used for separating groups of digits. For ease of reading digits should be grouped in threes counting from the decimal point towards the left and the right. Illustrations: Drawings and diagrams are to be in black India ink and should be about 18 cm wide. When submitting graphical representations avoid a fine grid if possible. Curves should be in heavy line to stand out. Lettering too should be bold as a reduction in size is often involved in the printing process. (A single column is 8.5 cm wide.) Numbering of tables should be in Roman numerals: I, 11, etc. and figures in Arabic numerals: Fig. 1, Fig. 2, etc. (Always use the abbreviation for figure.) Photographs should be black and white glossy prints. As a guide to the printer the author should indicate by means of notes in the typescript where tables and figures, etc. are to appear in the text. Paragraphs: A decimal system of numbering paragraphs may be used when the paper is long and complicated and there is a need for frequent reference to other parts of the paper. Proof correction: Galley proofs are sent to authors for the correction of printers' errors and not for the purpose of making alterations and additions which may be expensive. Should an author make alterations which are considered excessive, he may be required to pay for them. Standard symbols as laid down in British Standard 1219C should be used. SYNOPSIS It is most important that the synopsis should provide a clear outline of the contents of the paper, the results obtained and the author's conclusions. It should be written concisely and in normal rather than abbreviated English and should not exceed 250 words. While the emphasis is on brevity this should not be laboured to the extent of leaving out important matter or impairing intelligibility. Summaries simplify the task of abstractors and therefore should present a balanced and complete picture. It is preferable to use standard rather than proprietary terms. FOOTNOTES AND REFERENCES Footnotes should be used only when they are indispensable. In the typescript they should appear immediately below the line to which they refer and not at the foot of the page. References should be indicated by super-script, thus. . .1 . . .2. Do not use the word Bibliography. When authors cite publications of other societies or technical and trade journals, titles should be abbreviated in accordance with the standards adopted by this Journal. GENERAL The Council will consider the publication of technical notes taking up to three pages (maximum 3 000 words). Written contributions are invited to the discussion of all papers published in the Journal. The editors, however, are empowered by the Council to edit all contributions. Once a paper or a note has been submitted to the Institute, that document becomes the property of the Institute, which then holds the copyright when it is published. The Institute as a body is, however, not responsible for the statements made or opinions expressed in any of its publications. Reproduction from the Journal is permitted provided there is full acknowledgement of the source. These points should be borne in mind by authors who may submit their work to other organisations as well as to the Institute.